FEATURES OF IMPORTANCE FOR THE DEVELOPMENT OF PROJECT DOCUMENTATION IN THE SECTION OF PARK AND PUBLIC LAND DEVELOPMENT IN BULGARIA (World Science, 2025)
The organization of the territory is a system of measures, acts and actions of a factual and legal nature, which aim to create normal conditions for the use of the earth's surface for work, recreation and recovery of the population.